2004
DOI: 10.1016/s0002-9440(10)63293-2
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Macrophage Foam Cell Formation by αVβ3 Integrin

Abstract: The accumulation of macrophage foam cells in atherosclerotic lesions is associated with both initiation and progression of this disease. Scavenger receptors CD36 and SRA are the primary receptors responsible for conversion of macrophages into foam cells. Integrin alphaVbeta3 plays a role in the differentiation of several cell types, but its involvement in the transition of macrophages into foam cells and the potential role of this receptor in atherosclerosis have not been examined. Using an in vitro model of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
83
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 45 publications
(30 reference statements)
5
83
0
Order By: Relevance
“…RGD-Cy 5.5 not only strongly stained macrophages but also revealed a weaker signal associated with elastinrich fibers of the medium and vascular SMCs underlying the atherosclerotic plaque. These results were also congruent to the findings of Antonov et al (9), who demonstrated that a v b 3 integrin receptors, compared with endothelial cells, SMCs, and tissue macrophages, were highly upregu- lated in atheroma macrophages of early lipid (fatty streak) and advanced atherosclerotic lesions. However, endothelial cells and SMCs are known to express the vitronectin receptor on their surface (11) and to bind proteolytically active MMP-2, among other ligands.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…RGD-Cy 5.5 not only strongly stained macrophages but also revealed a weaker signal associated with elastinrich fibers of the medium and vascular SMCs underlying the atherosclerotic plaque. These results were also congruent to the findings of Antonov et al (9), who demonstrated that a v b 3 integrin receptors, compared with endothelial cells, SMCs, and tissue macrophages, were highly upregu- lated in atheroma macrophages of early lipid (fatty streak) and advanced atherosclerotic lesions. However, endothelial cells and SMCs are known to express the vitronectin receptor on their surface (11) and to bind proteolytically active MMP-2, among other ligands.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, monocytederived macrophages express high levels of integrins. Molecular imaging of integrins may, therefore, allow for noninvasive assessment of macrophage infiltration (9). Moreover, integrins constitute an important class of celladhesion receptors responsible not only for cell-matrix and cell-cell adhesion but also for inside-out and outside-in signal transduction.…”
mentioning
confidence: 99%
“…platelet-derived growth factor, fibroblast growth factor). ␣v␤3 is consistently detected on the macrophages in early and advanced human atherosclerotic lesions, and its expression is up-regulated by atherogenic stimuli (oxidized low-density lipoprotein, macrophage colonystimulating factor) in vitro (50). These reports suggest that sPLA2-IIA and ␣v␤3 co-exist in the inflammatory lesion and directly connect the pro-inflammatory action of sPLA2-IIA and ␣v␤3, the newly identified receptor of sPLA2-IIA.…”
Section: Discussionmentioning
confidence: 81%
“…Interestingly, a very recent report showed that monocyte CD36 expression and differentiation were downregulated when they bind to endothelial cells. 37 Therefore, binding-mediated monocyte CD36 regulation during cell-cell interactions seems to be cell-type specific, and the subendothelial space could be more favorable than blood vessel lumen for monocyte differentiation.…”
Section: Discussionmentioning
confidence: 99%